The Internal Control System of Universitas Klabat Indonesia: An Assessment - Sibilang, Linne (JBE (Journal of Business and Economics); Volume 8 No.1, 2009 JBE UNKLAB, 2009)
This study assessed the Internal Control system in Universitas Klabat, Manado-Indonesia, Internal Control itself is a process, affected by an entity's board of directors, management and other personnel, designed to provide reasonable assurance regarding the achievement of objectives in the following categories: (1) effectiveness and efficiency of operations, (2) reliability of financial reporting, (3) compliance with applicable laws and regulations.  It's a process, a means to an end, not an end in itself. It's affected by people and not merely policy, procedures, forms. It can provide only reasonable - not absolute assurance to achieve the objectives in one or more separate but overlapping categories.  Internal control consists of 5 interrelated components: (1) control environment, (2) risk assessment, (3) control activities, (4) information and Communication, and (5) monitoring.  Adopts the internal control-integrated framework concept, the concept that based on the Committee of Sponsoring Organization’s report, this study assess the Internal Control system in Universitas Klabat, Manado – Indonesia, and to what extent is, based on reasonable assurance, achieved the control objectives of effectiveness and efficiency of operation; reliability of financial reporting and compliance with applicable laws and regulation, and how responsive it to the changes in information technology and number of students.  The study concludes that Universitas Klabat implements internal control procedures and policies in aspects of control environment, risk assessment, control activities, information and communication control, and monitoring. Internal control of Universitas Klabat in its implementation has achieved the objectives of effectiveness operation, efficiency operation, reliability financial reporting, and compliance to the applicable laws and regulation based on the reasonable assurance. The system is relative highly responsiveness to the changes of information technology and number of students (volume of operation).